2008
DOI: 10.1108/00346650810920178
|View full text |Cite
|
Sign up to set email alerts
|

High trans fatty acid content in common Indian fast foods

Abstract: PurposeTrans fatty acids (TFA) are deleterious to health and can lead to multiple diseases. The purpose of this paper is to study their content in Indian sweets and snacks (fast foods).Design/methodology/approachThe paper used the food composition and analysis tables of the Indian National Institute of Nutrition to determine fatty acid composition of common nutrients. Separate tables provide nutrient composition of various Indian sweets and snacks including methods of preparation and amount of ingredients used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…However, many large fast-food companies do provide information on the TFA content of their foods, either in store or on their web sites. Moreover, in many lowand middle-income countries, the main source of TFAs is food purchased from street vendors and the unorganised food sector rather than pre-packaged food, 2,40,41 which may further limit the effectiveness of labelling regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, many large fast-food companies do provide information on the TFA content of their foods, either in store or on their web sites. Moreover, in many lowand middle-income countries, the main source of TFAs is food purchased from street vendors and the unorganised food sector rather than pre-packaged food, 2,40,41 which may further limit the effectiveness of labelling regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The Indian National Sample Survey Organization, India shows that consumption of beverages, biscuits, processed foods, salted snacks, prepared sweets and other purchased foods ranged from 100 -427 gm/ capita/day. Major dietary sources of TFA in India are deep fried fast foods such as samosas, baked products, packed snack foods, margarines and crackers [4,5]. The deep fried foods, unlike packaged snacks which display their nutritive value on packets, are commonly sold by vendors and difficult to be brought under regulations.…”
Section: Introductionmentioning
confidence: 99%
“…which are consumed widely. High TFA content (1.9% -53%) has been reported in Indian sweets and savories/snacks by Agrawal et al [5]. The authors derived the amount of TFA by calculating nutritive values of raw material such as oil and fats used in recipes, which is secondary in nature.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that TFA content of sweets varies from 0.3 − 17.7% and snacks from 0.1 − 19.8%, which translates into 1.9 − 5.3 fat energy % in sweets and 1.8 − 5.2 fat energy % in snacks (Agrawal et al, 2008). It was reported that six of ten types of chips examined contained more than 10% trans C18: 1 (in the range of 10.3 to 17.3% of the total fatty acid) and the other four had below 0.5%.…”
Section: Introductionmentioning
confidence: 99%